ANALISIS PERBANDINGAN KADAR SENYAWA NITRIT PADA SOSIS AYAM DAN SOSIS SAPI CURAH DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Bella Setya Ananda; Anita Agustina Styawan (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
In the current era of globalization, processed meat products are one type of fast food widely consumed by the public, especially sausages. Nitrite as a food preservative for processed meat, especially in sausages. However, it needs to be considered so as not to exceed the limit so that it does not adversely affect human health. This study aims to determine the levels of nitrite preservatives in bulk chicken sausages and bulk beef sausages circulating in online stores. The determination of nitrite levels in the samples was carried out using the UV-Vis spectrophotometric method using griess reagent and aquadestilata solution, the maximum wavelength obtained was 545 nm.Qualitative test results were positive for nitrite with pink color results. Quantitative tests using UV-Vis spectrophotometry obtained nitrite preservative levels equal to 3 replicates, the average bulk chicken sausage nitrite level was 1,44 mg/kg and the average bulk beef sausage level was 3,992 mg/kg. From the results of the study, nitrite levels in chicken sausage and bulk beef sausage circulating in online stores are suitable for consumption because nitrite levels in bulk chicken and beef sausages are not more than 30 mg/kg according to BPOM RI No. 36 of 2013 concerning nitrite preservatives in processed meat products.